Effect of Milk Origin and Seasonality of Yogurt Acid Whey on Antioxidant Activity before and after In Vitro Gastrointestinal Digestion - Eleni Dalaka; Georgios C. Stefos; Ioannis Politis; Georgios Theodorou (MDPI AG, 2023)
Yogurt acid whey (YAW) is a by-product of Greek strained yogurt production. The disposal of YAW constitutes an environmental problem, and given the increasing demand of Greek yogurt worldwide, its handling is a challenge. However, whey-derived peptides, resulting from microbial fermentation as well as those resulting from further hydrolysis during the digestion process, have been linked to enhanced biological activities. In this study, the antioxidant capacity of 33 samples of YAW obtained from Greek dairy companies of bovine, ovine or caprine origin was investigated using both cell-free and cell-based assays. The YAW samples, their in vitro digestion products (YAW-Ds) and a fraction of the digests (less than 3 kDa; YAW-D-P3) were assessed using four biochemical assays, namely ORAC, ABTS, FRAP and P-FRAP. Our data revealed a higher antioxidant capacity for digested samples compared with undigested samples, with all four methods. ORAC values after in vitro digestion were higher for the ovine samples compared to their bovine (YAW-D and YAW-D-P3) and caprine (YAW-D-P3) counterparts. Furthermore, the YAW-D-P3 fraction derived from samples collected in the summer months exhibited higher ORAC values when compared to the respective fraction from the winter months' samples. The cellular antioxidant activity of ovine YAW-D-P3 was improved in H2O2-treated HT29 cells compared to the control H2O2-treated cells. However, YAW-D-P3 could not trigger either the pathways involving the transcription factors NF-κB or NFE2L2 or the gene expression of SOD1, CAT and HMOX1 in LPS-challenged THP-1-derived macrophages. These results suggest that YAW, and particularly YAW from ovine origin, could be used as a natural source for its antioxidant potential in human and animal nutrition.